KEMAMPUAN MENULIS PUISI DENGAN PENDEKATAN KONTEKSTUAL - Rindiani, sisi; Deliani, Susy; Muliatik, Sri (Jurnal Bahasa Indonesia Prima (BIP), 2023)
The purpose of this study was to describe the methods, media, and student responses in learning poetry in class X SMK PAB 10 Patumbak. This research was conducted using a descriptive qualitative method. Data collection techniques are observation, essay tests, and documentation. The research data is information about poetry learning in class X, with 30 students in the experimental class and 30 students in the control class; data sources are from researchers, students, and events in learning to write poetry. The data analysis technique uses a contextual approach that is perfect for learning to write poetry in class X SMK PAB 10 Patumbak. The results of this study found that the learning method used by researchers was a contextual approach using essay tests. This method can arouse students' enthusiasm and interest in participating in learning, and the media researchers use relates to the surrounding natural environment. The results of student scores with an average achievement in control class learning with a score of 65, while experimental class learning with a score of 80 indicate that students' writing skills in contextual learning are better. Student responses were grouped into two, namely, positive and negative responses. Students' positive responses were shown by the activity of writing poetry in the experimental class using a contextual approach, namely being active in asking and answering questions posed by researchers, and the negative responses of students in the control class were seen by the lack of enthusiasm of students towards the use of the lecture method by researchers and the placement of class schedules at the end meetings where the condition of students is tired and hungry.